Malaysian public survey on the current carry-on luggage handling onboard commercial transport aircraft - I Romli, Fairuz; Hidayah Ariffin, Nur (International Journal of Engineering and Technology, 2018)
The current handling of carry-on luggage inside the aircraft cabin has led to several issues such as inefficient boarding and disembarking processes. Due to the number and size of current carry-on luggage, the boarding process has been slowed down due to aisle blocking and luggage overcrowding in the overhead storage bins. To improve this situation, an automated cabin luggage system has been proposed. A public survey has been conducted to explore the general passengers' perception of current carry-on luggage handling inside the cabin and to identify potential rooms for improvement that can be catered by the automated cabin luggage system. The responses obtained from the survey indicate that the current carry-on luggage handling does have several weaknesses that can be improved by the proposed automated system.Â Â